The Prospects of Islamic Education Curriculum: The Case of University of Abuja - Rafatu Abdulhamid (Ta'dib: Jurnal Pendidikan Islam, 2017)
The education Islamic studies play an important role of moulding and training the young and future leaders in their capacities as trained teachers. In order for them to discharge this role efficiently they need to be fully equipped with all the requisite knowledge of Islam throughout their educational career without any exception. However, the curriculum of Islamic education in Nigerian universities including University of Abuja is in dire need of improvement and modification because it has been observed that, Islamic education students offer limited courses of Islamic studies. Also the contents of most Universities curriculum are static; they are not reviewed periodically to meet the yearning needs of our changing society. This makes learning old fashion and irrelevant. The implication of this is that such students may not have the efficiency to teach their students as expected. The study recommends the review of the curriculum to make Islamic studies more robust in scope and contents to the students. This is necessary as it exposes the students to more knowledge of Islam than the current curriculum. The methodology consists of both library materials and field work.  The paper recommends that the Islamic studies curriculum should be reviewed to accommodate relevant educational contents capable of equipping learners with the skills, competencies and orientations that could make them perform excellently.